1996
DOI: 10.1021/ie950383n
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Lime, Sulfur, and Iron from Gypsum and Pyrite Wastes

Abstract: Currently, gypsum and pyrite, two major wastes generated by the coal combustion industry, have to be land-filled. The feasibility of a new approach of recovery of lime, iron, and sulfur products from these wastes is discussed in the present work. By thermal decomposition of pyrite, 42% of the sulfur is recovered and pyrrhotite is produced. A thermodynamic analysis shows that the recovery of iron and lime from pyrrhotite and gypsum in a single-stage process is not feasible. Instead, the process has to consist o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…(2) and/ or (3), cannot initiate at temperatures lower than 645°C in the present study. Such behavior is in good agreement with the results of Marina et al 20) and Rosenqvist 24) who also reported that the iron production from a mixture of FeS, CaO, and C is thermodynamically feasible above 650 and 730°C, respectively. Therefore, the weight loss in sample heated to 645°C in 10 min is attributed to either the fully dehydration reaction, as confirmed by XRD analysis (Fig.…”
Section: Heating Profilesupporting
confidence: 92%
See 2 more Smart Citations
“…(2) and/ or (3), cannot initiate at temperatures lower than 645°C in the present study. Such behavior is in good agreement with the results of Marina et al 20) and Rosenqvist 24) who also reported that the iron production from a mixture of FeS, CaO, and C is thermodynamically feasible above 650 and 730°C, respectively. Therefore, the weight loss in sample heated to 645°C in 10 min is attributed to either the fully dehydration reaction, as confirmed by XRD analysis (Fig.…”
Section: Heating Profilesupporting
confidence: 92%
“…(4). Figure 9 shows the reduction degree of the FeS:CaO:C = 1:1:2 mixture during microwave heating of samples heated to 1 290°C and that of a mixture with a same mole ratio after conventional heating reported by Jha et al 1) and by Kutsovskaya et al 20) It was observed that the reduction degree of samples heated for 30 and 35 min is higher than 100%. Jha et al 1) reported also reduction degree over 100% and theorized that it is because of the drainage of liquid form pellet.…”
Section: Effect Of Microwave Heating On Reduction Degreementioning
confidence: 79%
See 1 more Smart Citation
“…FGD gypsum can also be used in agriculture 113 and can be treated to produce useful materials 114 such as lime, sulfur, and iron. 115 3.4. Sodium and Potassium Carbonate.…”
Section: Potash (Potassium Hydroxide)mentioning
confidence: 99%
“…On the other hand, the activation energy of 215 kJ in the upper temperature regime (T ≥ 1273 K) is comparable to the activation energy of 239 ± 18 kJ, for the reaction between CaS and CaSO4 [41] and this is because, the reduction calcination of CaSO4 to CaO and SO2 occurs via equations 26 -28 [15]. The SO2 gas from equation 28 may react with the metal oxides according to equation 29.…”
mentioning
confidence: 99%